Filmische Zeugenschaft im Abseits Kulturelle Dekolonisierungsprozesse und Dokumentarfilme zwischen Mosambik und Portugal - Stock, Robert (Post_Koloniale Medienwissenschaft, 2018)
The first fundamental analysis of a cinematic testimony of the cultural decolonization processes between Mozambique and Portugal.